2005
DOI: 10.1111/j.1469-7580.2005.00491.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rhesus monkey superior olivary complex by calcium binding proteins and synaptophysin

Abstract: This study was performed in order to characterize the main nuclei of the rhesus monkey superior olivary complex by means of antibodies against the calcium binding proteins parvalbumin, calbindin and calretinin and the synaptic vesicle protein synaptophysin. These markers revealed the neuronal morphology and organization of nuclei located within the rhesus monkey superior olivary complex. The architectural details included the distribution of axonal terminals on neurons. The medial superior olivary nucleus was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 77 publications
(158 reference statements)
1
35
0
Order By: Relevance
“…Previous immunohistochemical study in the SOC of adult rhesus monkey demonstrated that the MNTB soma was encircled by a dense assembly of synaptophysin-positive terminals, which corresponded to the calyces of Held (Bazwinsky et al, 2005). In both preterm and term baboon neonates, the calyx of Held terminal exhibited thick, finger-like processes, as observed in adult rhesus monkey.…”
Section: Developmental Transitions In Inhibitory and Excitatory Inputmentioning
confidence: 82%
See 2 more Smart Citations
“…Previous immunohistochemical study in the SOC of adult rhesus monkey demonstrated that the MNTB soma was encircled by a dense assembly of synaptophysin-positive terminals, which corresponded to the calyces of Held (Bazwinsky et al, 2005). In both preterm and term baboon neonates, the calyx of Held terminal exhibited thick, finger-like processes, as observed in adult rhesus monkey.…”
Section: Developmental Transitions In Inhibitory and Excitatory Inputmentioning
confidence: 82%
“…Preterm baboons were delivered at 67% of gestation at the Texas Biomedical Research Institute in San Antonio. Preterm baboon care was recently described in detail (Blanco et al, 2013). Briefly, term baboons were naturally delivered (at 185 d GA), whereas preterm baboons were delivered via cesarean section at 125 Ϯ 2 d GA (67% of GA) and were intubated immediately after birth and chronically ventilated for a planned survival of 14 d in a neonatal intensive care unit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CB-IR neurons were prominent in principal neurons of the MNTB throughout different mammalian species, e.g., humans [Kulesza, 2014], rhesus monkeys [Bazwinsky et al, 2005], bats [Zettel et al, 1991], cats [Adams and Mugnaini, 1990;Matsubara, 1990], chinchillas [Kelley et al, 1992], rats [Webster et al, 1990;Friauf, 1994], and guinea pigs [Caicedo et al, 1996]. Likewise, CB-IR neurons were observed in the medial superior olive (MSO) of the bat [Zettel et al, 1991], whereas CB-IR neurons were not detected in the adult rat [Friauf, 1994], guinea pig [Caicedo et al, 1996], and cat [Adams and Mugnaini, 1990;Matsubara, 1990].…”
Section: Discussionmentioning
confidence: 95%
“…Relative to key functions in the auditory brain stem, CaBPs, e.g., calbindin D28k (CB), parvalbumin (PV), and calretinin (CR) distributions were broadly investigated to elucidate expression patterns in different SOC nuclei as well as distinct neuronal morphology by using immunohistochemistry in humans [Bazwinsky et al, 2003;Kulesza, 2014], rhesus monkeys [Bazwinsky et al, 2005], bats [Vater and Braun, 1994], rats [Lohmann and Friauf, 1996], mice [O'Neill et al, 1997], guinea pigs [Caicedo et al, 1996], gerbils, and opossum [Bazwinsky-Wutschke et al, 2016]. Ebbers et al [2015] validated that targeted deletion of Ca v 1.2 in the auditory brain stem resulted in postnatal cell death and a decrease in volume and cell numbers of auditory nuclei although auditory brain stem responses were nearly normal [Ebbers et al, 2015].…”
Section: Introductionmentioning
confidence: 99%